An analysis of feminism in the movie â€œThe Hunting Groundâ€ reviewed from the semiotics of John Viske - Fabianti, Rachmi Herdini; Putra, Fajar Dwi (Universitas Ahmad Dahlan, 2021)
The Hunting Groundâ€ is a documentary movie which tells about the sexual violence in United States colleges. The story is about the new college students, especially women who became the targets of rape and sexual violence. It is a pity because the colleges always ignore and do not respond the report from the victims. The aim of this study is to determine the representation of feminism in the